Cuntz Splice invariance for purely infinite graph algebras - Bentmann, Rasmus (MATHEMATICA SCANDINAVICA, 2018)
We show that the Cuntz Splice preserves the stable isomorphism class of a purely infinite graph $C^*$-algebra with finitely many ideals.